Nanostructure and doping engineering of ZnCoP for high performance electrolysis of water. (June 2020) - Dai, Meizhen; Zhao, Depeng; Liu, Hengqi; Tong, Yongli; Hu, Pengfei; Wu, Xiang
Abstract: To design rationally bi-functional electrocatalysts with high efficiency and rich defects for overall water splitting is greatly desirable. However, some electrode materials often exhibit slow electrons transportation. To address above issues, Mo doped ZnCoP products with high electrocatalytic activities are fabricated through a convenient hydrothermal and phosphating route. The as-obtained Mo-ZnCoP-0.5 products show HER activities with an overpotential of 153.1 mV at −10 mA cm −2 and the overpotential of 280 mV at 50 mA cm −2 for OER. In addition, the as-prepared electrocatalysts present overall water splitting performances with a cell voltage of 1.51 V at 50 mA cm −2, revealing that Mo element doping can effectively regulate the electronic structures of ZnCoP products due to the formation of many defects. Graphical abstract: Image 1 Highlights: We fabricate Mo doped ZnCoP nanowires for overall water splitting through a two-step approach. The as-obtained Mo-ZnCoP-0.5 samples present a HER performance with an overpotential of 153.1 mV at −10 mA cm −2 . The samples possess an overall water splitting performance with a cell voltage of 1.51 V.